Price elasticity of water demand considering scarcity and attitudes. (August 2019) - Garrone, Paola; Grilli, Luca; Marzano, Riccardo
Abstract: The effectiveness of price as a water conservation measure remains an open empirical issue and relevant policy question. We conduct a meta-regression analysis to single out location and community traits that boost or depress the price elasticity of residential demand. Our results reveal that water scarcity exerts significant influence on price elasticity. More specifically, if water scarcity is severe, household responsiveness to prices decreases, though this effect is attenuated in environmentally concerned communities. Highlights: We conduct a meta-regression that summarizes 615 estimates of the price elasticity of residential water demand. Our results reveal that water scarcity is a significant driver of price elasticity. When water scarcity is harsh, residents' sensitivity to price measures decreases. The scarcity effect on price elasticity is mitigated in environmentally concerned communities.